PENGEMBANGAN E-LKPD BERBASIS VIRTUAL LABORATORY PhET DILENGKAPI KETERAMPILAN PROSES SAINS PADA MATERI ASAM BASA (Research And Development) - Febri Nurason; Hermansyah Amir; Nadia Amida (ALOTROP, 2022)
This study aims to determine the feasibility, student responses and the completeness of science process skills on the PhET E-LKPD with acid-base material. This research is a research and development that adapts the 4D model which is limited to the third stage, namely the development stage. The data in this study were obtained from the results of interviews, material and media validation questionnaires and student response questionnaires. The population in this study were students of class XI MIPA 4 SMAN 3 Bengkulu City with 17 people. The results of the material and media test of E-LKPD PhET obtained values of 93.18% and 88.64% which are included in the very feasible category dan while the results of the student response test to the PhET E-LKPD obtained a value of 89.26% which is included in the very feasible category. The prepared PhET E-LKPD has been equipped with aspects of science process skills such as observing, formulating hypotheses, designing experiments, taking measurements, interpreting data, concluding and communicating. So it can be concluded that the PhET E-LKPD is suitable for use in the learning process. Keywords : E-LKPD, PhET, Acid-Base